Road Cross-Section Width and Free-Flow Speed in Two-Lane Rural Highways - Pedro Melo (2012)
Speed choice is strongly influenced by geometric road features. In this work, the influence of lane and shoulder widths on free-flow speed was studied with the driving simulator DriS at the University of Porto in Porto, Portugal. To evaluate how speed was influenced by the cross section, this study investigated the possible influence of the order of magnitude of the practiced speeds on the effects of variations in lane and shoulder widths. Two types of roads with different base speeds were considered. The roads were presented to drivers on a driving simulator. The validity of the data obtained in the simulator was confirmed through a comparative analysis of the registered speeds in the real environments for the equivalent simulator conditions at six points of control. The lane and shoulder widths from which the free-flow speed was no longer conditioned by the dimensions of the road's cross section were obtained, as well as the reduction in speed associated with smaller widths. Contrary to what was suggested by the Highway Capacity Manual 2010, the individual effects of variations in lane and shoulder widths were not cumulative; greater impacts on free-flow speed were obtained by their simultaneous variation.